Complete remission of NUP98 fusion-positive acute myeloid leukemia with the covalent menin inhibitor BMF-219, icovamenib - Hetty E. Carraway; Joy Nakitandwe; Alexandru Cacovean; Yan Ma; Brian Munneke; Ganesh Waghmare; Clarissa Mandap; Uzma Ahmed; Nicole Kowalczyk; Thomas Butler; Stephan W. Morris (Haematologica)
Not available.